Conceptualisation and development of consumer-based corporate social responsibility scale - Quah, Kheng Siong (2015)
Various definitions and scales to measure corporate social responsibility (CSR) have been proposed, and most of them are derived from the firm’s perspective. Given consumer as one of the significance beneficiaries of firms’ CSR, the accuracy of firm-based CSR scales to measure perception of consumer about CSR is uncertain. In this thesis, literature in the fields of CSR, benefits of CSR, measures of CSR, CSR theories and the stakeholder theory are discussed. Based upon this literature, a new CSR scale that provides a measurement of CSR from the consumer’s perspective is developed. Mixed method research consisting of two phases of research was carried out to develop this new scale. In the first phase, qualitative inquiry was carried out to collect respondents’ descriptions about CSR through personal interview. In particular, 14 personal interviews sessions were conducted with the following groups: general consumer,consumer association and firm. Respondents’ descriptions about CSR were used in reference with CSR literature to generate a pool of items for this new scale. In the second phase, quantitative inquiry was carried out to examine the reliability and validity of the items derived from the qualitative inquiry. The consumer-based CSR scale was tested against 508 respondents, who worked in firms around Klang Valley, Malaysia. The domains of consumer-based CSR scale identified through the exploratory and confirmatory factor analyses were ascertained to be reliable and valid. Results of factor analyses indicated that domains which influence consumers to form their CSR understanding of CSR were firms’ product, environmental and philanthropic responsibilities. The newly developed consumer-based CSR scale suggests a new composition of CSR from the consumer’s perspective. This new composition of CSR reflects the perception of consumer pertains with CSR. Moreover, this consumer-based CSR scale provides a more accurate measurement for CSR researchers to identify the perception of consumer about CSR when compare with other firm-based CSR scales.